Gen Y Online Shopping Intention towards Electronic products in Kuala Lumpur - Salum, Ali Salum (2016)
The purpose of this study is to determine the investigation that influences the intention of online purchase of electronic products among the Gen Y in Kuala Lumpur. The development of technology, which spark the growth of Internet hence changing shopping pattern from traditional to online shopping. The study used Theory of perceived risk and Technology acceptance model (TAM). The study address key issues, which might have positive relationship towards online shopping intention towards electronic products which are perceived risk, ease of use and usefulness. The sample size comprises of 250 participants. Correlation design, which is descriptive in nature, will be used to analyse the study and multiple linear regressions. The independent variable of the study is expected to have positive significant relationship with the dependent variable.